2017
DOI: 10.1556/2054.01.2017.009
|View full text |Cite
|
Sign up to set email alerts
|

Subjective effectiveness of ibogaine treatment for problematic opioid consumption: Short- and long-term outcomes and current psychological functioning

Abstract: Background and aimsVery few studies have reported the effectiveness of ibogaine as a treatment for chronic opioid use. Therefore, this study evaluated the acute subjective effects of ibogaine, outcomes on problematic opioid consumption, and the long-term associations with psychological functioning.MethodsUsing online data collection, 88 patients who received ibogaine treatment in Mexico between 2012 and 2015 completed our survey.ResultsMost participants (72%) had used opioids for at least 4 years and 69% repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 21 publications
(24 reference statements)
2
33
0
7
Order By: Relevance
“…Ibogaine reportedly has helped people transition from heroin and cocaine to sobriety ( Alper et al, 2008 ; Brown and Alper, 2017 ; Davis et al, 2017 ; Noller et al, 2018 ). Because of ibogaine’s oneiric effects and complex pharmacokinetics, we originally suggested that noribogaine should be advanced for opioid detoxification to promote a transition to abstinence ( Mash et al, 2000 , 2001 ; Mash, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ibogaine reportedly has helped people transition from heroin and cocaine to sobriety ( Alper et al, 2008 ; Brown and Alper, 2017 ; Davis et al, 2017 ; Noller et al, 2018 ). Because of ibogaine’s oneiric effects and complex pharmacokinetics, we originally suggested that noribogaine should be advanced for opioid detoxification to promote a transition to abstinence ( Mash et al, 2000 , 2001 ; Mash, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ibogaine may help opioid dependent patients to transition to sobriety and to establish a substance-free recovery because the oneirophrenic effects have therapeutic benefit as an adjuvant to psychotherapy ( Alper et al, 1999 ; Davis et al, 2017 ; Mash, 2018 ). The elicitation narratives described in this report suggest that ibogaine may promote harm reduction following detoxification from opioids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 Ibogaine was used in France for over 30 years as an anti-depressant and a stimulant until the mid-1960s. 25 Ibogaine treatment is reported to alleviate a spectrum of mood and anxiety symptoms 25 28 and is associated with self-reported improvements in cognitive functioning in individuals with substance use disorders. 29 31 During treatment, ibogaine allows the evocation and reprocessing of traumatic memories and occasions therapeutic and meaningful visions of spiritual and autobiographical content, 26 , 29 , 30 , 32 which are of central relevance in addressing PTSD-related psychological content.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Ibogaine treatment is reported to alleviate a spectrum of mood and anxiety symptoms 25 28 and is associated with self-reported improvements in cognitive functioning in individuals with substance use disorders. 29 31 During treatment, ibogaine allows the evocation and reprocessing of traumatic memories and occasions therapeutic and meaningful visions of spiritual and autobiographical content, 26 , 29 , 30 , 32 which are of central relevance in addressing PTSD-related psychological content. The benefits of ibogaine may be associated with its effects on serotonin and dopamine transporters, sigma, N-methyl-d-aspartate, nicotinic acetylcholine, and opioid receptors, 29 , 33 , 34 and the production of glial-derived neurotrophic factors 35 and brain-derived neurotropic factor 36 which are identified sites of interest in the treatment of cognitive impairment in neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%